Strengthening Discipline Character & Student Learning Outcomes through Implementation of Portfolio Assignments in E-learning - Edy Herianto (Graduate School of Universitas Negeri Malang, 2022)
Abstract: Discipline character cannot be realized without continuous habituation. In portfolio assignment-based e-learning, students can practice habituation. If the habituation of discipline is continuously carried out through the portfolio lever, students will get a strengthening of the character of discipline and optimal learning outcomes. By using qualitative research type phenomenology on 42 students in the PIPPKn course, this research aims to answer how to implement e-learning based on portfolio assignments that have an impact on strengthening the character of discipline and student learning outcomes? Data were obtained through observations, interviews, questionnaires, and tests. Data analysis was carried out qualitatively with descriptive percentages. The results show that portfolio assignments can familiarize students with discipline in completing assignments. This habit has an impact on the acquisition of significant positive learning outcomes.Abstrak: Karakter disiplin tidak dapat terwujud tanpa pembiasaan yang terus menerus. Dalam e-learning berbasis tugas portofolio, siswa dapat mempraktekkan pembiasaan. Jika pembiasaan disiplin terus dilakukan melalui pengungkit portofolio, siswa akan mendapatkan penguatan karakter disiplin dan hasil belajar yang optimal. Dengan menggunakan jenis penelitian kualitatif fenomenologi pada 42 mahasiswa mata kuliah PIPPKn, penelitian ini bertujuan untuk menjawab bagaimana penerapan e-learning berbasis tugas portofolio yang berdampak pada penguatan karakter disiplin dan hasil belajar mahasiswa? Data diperoleh melalui observasi, wawancara, angket, dan tes. Analisis data dilakukan secara kualitatif dengan deskriptif persentase. Hasil penelitian menunjukkan bahwa penugasan portofolio dapat membiasakan siswa disiplin dalam menyelesaikan tugas. Kebiasaan ini berdampak pada perolehan hasil belajar positif yang signifikan.